ChemInform Abstract: CsHgInS3: A New Quaternary Semiconductor for γ‐Ray Detection. Issue 9 (5th March 2013) - Li, Hao; Malliakas, Christos D.; Liu, Zhifu; Peters, John A.; Jin, Hosub; Morris, Collin D.; Zhao, Lidong; Wessels, Bruce W.; Freeman, Arthur J.; Kanatzidis, Mercouri G.
Abstract The new layered title compound is synthesized by solid state reaction of In, HgS, Cs2S, and sulfur (silica tube, 600 °C for 24 h, 800 °C for 8 h; 70% yield).